EVALUASI TOLERANSI TANAMAN KEDELAI (Glycine max (L.) Merrill) GENERASI M3 HASIL RADIASI SINAR GAMMA TERHADAP SALINITAS - Rapi Rapi Simbolon1; Emi Harso Kardhinata; Yusuf Husni (Jurnal Agroekoteknologi, 2013)
The objective of the research is to know the tolerance of M3 soybean generation radiated by gamma ray to salinity. The research  was conducted on the Experimental Farm Faculty of Agriculture, University of North Sumatra,, from December 2011 – March 2012. Randomized block design was used with two treatments i.e : population of M3 soybean (0, 10, 20, 30 krad per plant) and NaCl concentration (0, 1500, 3000, 4500 ppm). Parameters measured were plant germination, viability, high of plant, the number of node per plant, the number of branch, root longth, weigh of dry root, weigh of dry leaves, the number of pods per plant, the number of empty pods per plant and weigh of 100 seed. M3 soybeans showed significant diffrent on root longth and weigh of dry root. NaCl concentration affect were significantly to plant germination and viability.The interaction between population M3 soybeans and NaCl concentration were significantly to the number of node per plant, the number of branch, weigh of dry leaves, the number of pods per plant, the number of empty pods per plant and weigh of 100 seed.   Key words: tolerance, salinity, M3 generation, soybean